PASSENGERS’ DEVIANT BEHAVIOR MAPPING IN DURI TRAIN STATION - Zubair, Ahmad; Sumadio, Widyawati; Putri, A.R.Z (UI Scholars Hub, 2022)
The lack of train station facilities influences the passengers' deviant behavior. This paper aims to analyze the Pattern of Commuter Line passengers' behavior in Duri Station. In collecting data regarding the passengers' behavior, we observed the passengers using the Place Centeres Mapping method. This observation technique aims to understand how people utilize or accommodate their behavior at a particular time and location in the train station. This research model is divided into two stages. The first stage consists of observation and semi-structured interviews with the passengers. The second stage examines the passengers' behavior based on location within the train station. In this study, we analyzed the data through data triangulation and spatial analysis, along with several theoretical discussions about where, when, and why the passengers conduct deviant behavior. The results showed that passengers' deviant behavior was based on three components of the station zones: the arrival zone, main facilities zone, and platform zone. The main facilities and platform zones are more prone to passengers' deviant behavior. The most common deviant behaviors are pickpocketing and verbal harassment, whereas the least deviant is sitting on the platform floors. These deviant behaviors occur mainly due to the fact that during peak hours, there are less security guards than there are passengers.